PENGEMBANGAN MEDIA VIDEO ANIMASI PADA MUATAN MATEMATIKA KD 3.3 di KELAS III SEKOLAH DASAR - Lika Apreasta; Muhammad Subhan; Reza Silviani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This understanding is motivated by students in difficulty understanding the mathematics learning process, because mathematics learning contains many numbers and is in class with counting lessons, causing students to be bored and difficult to understand. Learning material delivered during the learning process, makes the objectives of learning not achieved properly. This type of research is a Research and Development (R&D) research using the ADDIE model which consists of several stages (Analyze, Design, Development, Implementation, and Evaluation), the test subjects are grade III students of SDN 11 Sitiung. Data collection instruments use validity instruments, practicality instruments, and effectiveness instruments. The assessment instrument is validated by three validators, namely language, graphics, and content validators, then the practicality sheet is determined by practitioners, namely teachers and grade III students. Meanwhile, the effectiveness of animated videos is determined from the learning outcomes of grade III students of SDN 11 Sitiung using animated video media.The validation results carried out by three validators obtained an average validity value of 85.26% with a very valid category in the sense that animated video media for mathematics learning is suitable for use by students. The results of the practicality value of the educator response questionnaire obtained 87.5% with the very practical category, while the results of the practicality value of the student response questionnaire obtained an average of 85.5% with the very practical category, so that the educator and student respose questionnaires obtained an average of 86.5%, in the sense that it is easy to use by students and time efficient. The results of the effectiveness value of 11 students who participated in learning using animated video media developed on the 82% complete number calculation operation material which is categorized as very effective so that it is easy to use, in terms of time very efficient.